2022
DOI: 10.1039/d1ta10864f
|View full text |Cite
|
Sign up to set email alerts
|

A two-electron transfer mechanism of the Zn-doped δ-MnO2 cathode toward aqueous Zn-ion batteries with ultrahigh capacity

Abstract: Neutral aqueous Zinc-ion batteries (ZIBs) have attracted considerable attention due to their safe and green features. As one typical cathode, birnessite MnO2 (δ-MnO2) suffers from low conductivity and structural instability,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…After compositing with rGO, the contribution of inserted H þ and Zn 2þ to the capacity increases greatly at the same time. This may be related to oxygen vacancies, [10,27] two-electron reactions, [15,28] or interfaces. [29,30] It is also reported that this super-capacity phenomenon has also been found in vanadiumbased composite materials, [30] and the detailed mechanism still needs to be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…After compositing with rGO, the contribution of inserted H þ and Zn 2þ to the capacity increases greatly at the same time. This may be related to oxygen vacancies, [10,27] two-electron reactions, [15,28] or interfaces. [29,30] It is also reported that this super-capacity phenomenon has also been found in vanadiumbased composite materials, [30] and the detailed mechanism still needs to be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of heteroatoms, especially cations, has been proved to be an effective way to boost reaction kinetics and suppresses the irreversible lattice distortion of MnO 2 . 9,40,41 The modification of cations (La 3+ , 36 K + , 37 Zn 2+ , 42 etc .) is often accompanied by the formation of oxygen vacancies, which is important for modifying the ion migration properties of MnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[25][26] Among various metal ions, the low valence cation of Zn 2 + has been demonstrated to effectively enhance intrinsic conductivity and boost electrolyte ion diffusion kinetics by the construction of oxygen vacancies as compared with other metal ions when intercalating into the manganese oxide materials, which can finally enhance the corresponding electrochemical performances. [27][28] However, only a very few reports relating to the usage in AZIB applications have been published, such as Zn doped δ-MnO 2 with an ultrahigh reversible capacity of 455 mAh g À 1 at 25 mA g À 1 and Zn 2 + stabilized layered-type MnO 2 structure with high rate capability of 124 mAh g À 1 at 3.0 A g À 1 . [27,29] In addition, specific capacitance depends not only on the electrical conductivity and ion transport properties but also on the effective contact area between the electrode materials and electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28] However, only a very few reports relating to the usage in AZIB applications have been published, such as Zn doped δ-MnO 2 with an ultrahigh reversible capacity of 455 mAh g À 1 at 25 mA g À 1 and Zn 2 + stabilized layered-type MnO 2 structure with high rate capability of 124 mAh g À 1 at 3.0 A g À 1 . [27,29] In addition, specific capacitance depends not only on the electrical conductivity and ion transport properties but also on the effective contact area between the electrode materials and electrolytes. For that, in terms of the improved specific capacity, MnO x with the three-dimensional (3D) framework has an advantage over the present MnO 2 with other morphologies due to its enhanced electrolyte-accessible surface area, which facilitates easy access of electrolytic ions into the interior of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation